'I will handle it personally': The neo-patrimonial rhetoric of the Czech Prime Minister in the times of COVID-19. Issue 3 (3rd July 2022) - Naxera, Vladimír; Stulík, Ondřej
ABSTRACT: This paper contributes to the contemporary discussion about the political consequences of the COVID-19 pandemic situation. The goal of the text is to identify and analyze the neo-patrimonial rhetoric of Czech Prime Minister Babiš in connection with his handling of the pandemic. Using the quantitative and qualitative content analysis, we show, that Babiš' rhetoric has shifted after the beginning of the crisis from an anti-elite position to a neo-patrimonial (as a brand-new type of populism in the European context). The purpose of this text is to point out the rhetoric shift bounds to problematic consequences on the exercise of his function and the neutrality of the bureaucratic apparatus, which must apply during states of emergency.